MENINGKATKAN HASIL BELAJAR GEOGRAFI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COURSE REVIEW HORAY - Yuniarti (EDUCATE, 2023)
The subjects in this research were class XII-IIS3 students at SMA Negeri 2 Tebing Tinggi. 2023-2024 Academic Year, totaling 35 students. The instruments used were teacher and student observation sheets as well as test scores on student learning outcomes. The data collection technique uses student learning outcomes tests. The data that has been collected is analyzed using comparative descriptive, namely: comparing learning outcomes before the research is carried out and after the research is carried out, namely after using the Course Review Horay learning model. Based on the results of the initial test before the research was carried out on 35 students, it showed that only 12 students completed (KKM 75.00), the level of classical learning completeness was only 34.28%, with an average class score of 68.60. Test results on 15 students completed the first cycle and classical learning completion was 77.14%, with an average class score of 77.90. Meanwhile, the test results in cycle II experienced a significant increase, namely as many as 35 students who completed classical learning reached 97.14% with an average class score of 90.60. It can be concluded that using the course review horay learning model can improve student learning outcomes in class XII-IIS3 SMA Negeri 2 Tebing Tinggi for the 2023-2024 academic year.